THE EDUCATION IN ERA SOCIETY 5.0 - Nova Jayanti Harahap; Christine Herawati Limbong; Elida Florentina Sinaga Simanjorang (JURNAL EDUSCIENCE, 2023)
Abstract The era of society 5.0 is a concept of life that emphasizes and focuses on social responsibility and improving the quality of life that is more advanced and discoveries of new innovation centers compared to the industrial revolution 4.0 which is more focused on technology. This research is a qualitative research using the literature study method. The method used is by collecting information or data through relevant books, journals or articles. Era Society 5.0 makes society a source of innovation that can solve various situations and social problems with the help of the integration of physical and virtual spaces. Era Society 5.0 in the world of education needs to increase creativity and skills by applying soft skills and hard skills using various increasingly sophisticated technologies. Because of this, students are expected to be able to think critically and be communicative in developing skills. Society 5.0 plays a big role in influencing the world of education and brings big influences and changes to schools, teachers to students. The advancement of science in the field of technology makes us ready to face changes in the world, especially in the field of education. One of these changes is Society 5.0. Society 5.0 is a human being who can solve various challenges and social problems by utilizing various innovations that were born in the era of the industrial revolution 4.0 and are centered on technology. Education in the era of society 5.0 requires everyone to be more creative, innovative, productive, adaptive and also competitive. In addition, education is needed about life skills known as 4C (Creativity, Critical Thinking, Communication, Collaboration.)Keywords: Era Society 5.0, The Quality of EducationAbstrak Era society 5.0 merupakan konsep hidup yang menekankan dan fokus pada tanggung jawab sosial serta peningkatan kualitas hidup yang lebih maju dan penemuan-penemuan pusat inovasi baru dibandingkan dengan revolusi industri 4.0 yang lebih fokus pada teknologi. Penelitian ini merupakan penelitian kualitatif dengan metode study literature, Metode yang digunakan yaitu dengan cara mengumpulkan informasi atau data melalui buku, jurnal atau artikel yang relevan. Era Society 5.0 menjadikan masyarakat sebagai sumber inovasi yang dapat memecahkan berbagai situasi maupun masalah sosial dengan bantuan integrasi ruang fisik dan virtual. Era Society 5.0 dalam dunia pendidikan perlu dengan meningkatkan kreatifitas dan ketrampilan dengan menerapkan soft skill dan hard skill dengan menggunakan berbagai teknologi yang semakin canggih. Karena hal tersebut peserta didik diharapkan mampu berpikir kritis dan komunikatif dalam mengambangkan skill. Society 5.0 berperan banyak dalam mempengaruhi dunia pendidikan serta membawa pengaruh dan perubahan besar bagi sekolah, tenanga pengajar hingga peserta didik. Majunya ilmu pengetahuan dibidang teknologi membuat kita untuk siap menghadapi perubahan dunia terutama dalam bidang pendidikan. Salah satu bentuk perubahan tersebut yaitu Society 5.0. Society 5.0 adalah manusia  yang dapat menyelesaikan berbagai tantangan dan permasalahan sosial dengan memanfaatkan berbagai inovasi yang lahir di era Revolusi industri 4.0 dan berpusat di teknologi.  Pendidikan di era society 5.0 menuntut setiap orang untuk lebih kreatif, inovatif, produktif, adaptif dan juga kompetitif. Selain itu, diperlukan pendidikan tentang kecakapan hidup yang dikenal dengan istilah 4C (Creativity, Critical Thinking, Communication, Collaboration.)Kata Kunci: Era Society 5.0,  Pendidikan Berkualitas